Understanding the Codex Standard to Ensure Safety and Quality of Palm Oil - Purwiyatno Hariyadi (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2021)
Indonesia is the number one producer and exporter of palm oil globally. About 85% of palm oil is used for food applications. Consequently, issues related to food safety and nutrition have always been a major concern, both for producers and consumers of palm oil. In this respect, the palm oil industry must put serious effort to comply with food safety and quality standards, such as those of Codex standards, especially specified at Codex Standard for named vegetable oils (CXS 210-1999).